The concentration of reproduction in cohorts of women in Europe and the United States - Shkolmkov, V. M.; Andreev, E. M.; Houle, R.; Vaupel, J. W.
gráfs., tbls.
pp. 67-99
Keywords: Estados Unidos de America; Europa; Mujeres; Fecundidad; Paises Desarrollados; Siglo XX